Survival and care practices of periviable births of <24 weeks’ gestation—a single center retrospective study in China, 2015–2021 - Chen, Chun; Xiong, Xiaoyun; Zhao, Jie; Wang, Meiqi; Huang, Zhifeng; Yang, Chuanzhong (Frontiers in Pediatrics, 2022)
Background:Though many studies have published their short- or long-term survival, very few have described the care practices and the course of stay of these neonates in detail. Our objective was to examine survival and clinical practices among preterm infants born at ≤23 weeks' gestational age (GA) in a high-income city in China, from 2015 to 2021. Methods: Retrospective study of preterm infants ≤23 weeks GA in a level 3 neonatal intensive care unit in China, over a period of 7 years (2015–2021). Survival to discharge and major morbidity (ie, bronchopulmonary dysplasia, grades III-IV intraventricular hemorrhage, sepsis, or severe retinopathy of prematurity) were measured. Results: A total of 32 periviable infants were included, with median GA of 23.0 weeks (range 21.4～23.6) and mean (SD) birth weight of 497(94)g (range 350～720); 18 infants (56.3%) were female. Antenatal corticosteroids were used in 62.5%, and 100%were vaginal birth. In the delivery room, surfactant was prescribed for 46.9% (15 of 32) of the infants, and postnatal dexamethasone (≥2courses) was prescribed to 25.0% (8 of 32) of the infants. A total of 68.9% (22) of the infants received active care, while none of the infants born at 21 weeks of gestation survived until discharge, the survival rates were 25.0%(3 of 12) for infants born at 22 weeks, 58.8%(10 of 17) at 23weeks.The incidences of the major morbidities were bronchopulmonary dysplasia 76.9% (10 of 13); retinopathy of prematurity (Stage ≥3) 38.5% (5 of 13)；late-onset sepsis 23.1% (3 of 13);intraventricular hemorrhagegrade(grade Ⅲ-Ⅳ)15.4%(2/13) and necrotizing enterocolitis(≥stage IIa )15.4% (2/13) among infants who alived at discharge. Logistic regression analysis showed that apgar score at 5‐minute (OR=2.007, 95%CI 1.031 -3.906, P<0.05) increased the risk of death, while the increase in gestational age (OR=0.238, 95%CI 0.060-0.936, P<0.05), antenatal use of steroids (OR=0.287, 95%CI 0.106-0.778, P<0.01), premature rupture of membranes (OR=0.141, 95%CI 0.024 -0.847,P=0.032), could decrease the risk.